1986
DOI: 10.1007/bf00393465
|View full text |Cite
|
Sign up to set email alerts
|

Congo red absorption and cellulose synthesis by Rhizobiaceae

Abstract: Congo red uptake by Rhizobium colonies from yeast extract-mannitol-mineral salts-Congo red-agar plates was related with the cellulose content in the cell capsule of the bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 10 publications
3
14
0
3
Order By: Relevance
“…These strains formed white colonies on agar plates with Congo red, confirming that binding of the stain by the mutant R201 resulting in red colonies is correlated to high production of cellulose fibrils. Although it has been reported that Congo red also can bind to outer-membrane proteins of various Gram-negative, animal pathogenic bacteria (Theisen et al, 1993), our data support the observation by Zevenhuizen et al (1986) that in Rhixobium the Congo red binding is related to the cellulose content of the bacteria. Thus in all subsequent experiments (e.g.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These strains formed white colonies on agar plates with Congo red, confirming that binding of the stain by the mutant R201 resulting in red colonies is correlated to high production of cellulose fibrils. Although it has been reported that Congo red also can bind to outer-membrane proteins of various Gram-negative, animal pathogenic bacteria (Theisen et al, 1993), our data support the observation by Zevenhuizen et al (1986) that in Rhixobium the Congo red binding is related to the cellulose content of the bacteria. Thus in all subsequent experiments (e.g.…”
Section: Resultssupporting
confidence: 87%
“…However, there are exceptions to this generalized behaviour, as reported by Zevenhuizen et al (1986). These authors showed that a few Rhizobium strains produced red to deep-red colonies on medium with Congo red and had cellulose contents of 1-10 % of their d r y weights.…”
Section: Resultsmentioning
confidence: 85%
“…In a set of preliminary experiments, we overexpressed celR mutated at Asp53 in the CheY domain (celRD53A) or at a key residue of the enzymatic GGEEF motif (celRE373A) in wild-type strain NTL7. We assessed the effects of these mutations on cellulose production by colony color on Congo red plates (45) and by growth properties in liquid media. As we described previously (22), compared to the parent, overexpressing wild-type celR resulted in increased Congo red binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Congo red binding is indicative of exopolysaccharides and some amyloid proteins (48,49) and suggests that atu1060 and atu1297 influence the production of such products. To test if the exopolysaccharide induced by overexpression of atu1297 or atu1060 was cellulose, the effects of pZLQatu1297 and pZLQatu1060 on NTL4(pTiC58) were examined by genetic manipulation and by quantification of total anthrone-positive material.…”
Section: Resultsmentioning
confidence: 99%